Digital governance and the reconstruction of the Indian anti-poverty system. (2nd October 2017) - Masiero, Silvia
Abstract: On a global scale, programmes of social protection for the poor are becoming increasingly computerised, and architectures of biometric recognition are being widely used in this respect. I research how these architectures, adopted in anti-poverty systems, structure ways to 'see the state' for citizens living in poverty. To do so I study India's Public Distribution System (PDS) in Kerala, which is augmenting its main food security scheme with the computerised recognition of its users. In the government's narrative, biometric technology is depicted as an optimal solution to the illicit diversion of PDS goods on the market. Nevertheless, according to the multiple narratives collected across the state, beneficiaries dispute this view in different ways because of the mixed effects of the new technology on their entitlements under the PDS. The government's capability to reconstruct its image through digital innovation is thus found to be constrained by citizens' perceptions derived from their encounters with the new technology of governance.